Engaging Sexual and Gender Minority (SGM) Communities for Health Research: Building and Sustaining PRIDEnet - Juno Obedin-Maliver; Carolyn Hunt; Annesa Flentje; Cassie Armea-Warren; Mahri Bahati; Micah Lubensky; Zubin Dastur; Chloe Eastburn; Ell Hundertmark; Daniel Moretti; Anthony Pho; Ana Rescate; et al. (Journal of Community Engagement and Scholarship, 2024)
Lesbian, gay, bisexual, transgender, queer, intersex, asexual, aromantic, and other sexual and/or gender minority (LGBTQIA+) communities are underrepresented in health research and subject to documented health disparities. In addition, LGBTQIA+ communities have experienced mistreatment, discrimination, and stigma in health care and health research settings. Effectively engaging LGBTQIA+ communities and individuals in health research is critical to developing representative data sets, improving health care provision and policy, and reducing disparities. However, little is known about what engagement approaches work well with LGBTQIA+ people. This paper describes the development of PRIDEnet (pridenet.org), a national network dedicated to catalyzing LGBTQIA+ community involvement in health research and built upon well-established community-engaged research (CEnR) principles. PRIDEnet’s relationship building and digital communications activities engage thousands of LGBTQIA+-identified people across the country and offer multiple low-threshold ways to participate in specific studies and shape research. These activities comprise a CEnR infrastructure that engages LGBTQIA+ people on behalf of other projects, primarily The PRIDE Study (pridestudy.org) and the National Institutes of Health’s All of Us Research Program (joinallofus.org/lgbtqia). Our impact, results, and lessons learned apply to those engaging communities underserved in biomedical research and include: the importance of building adaptable infrastructure that sustains transformational relationships long-term; implementing high-touch activities to establish trust and broad-reach activities to build large data sets; nurturing a team of diverse professionals with lived experiences that reflect those of the communities to be engaged; and maintaining CEnR mechanisms that exceed advice-giving and result in substantive research contributions from beginning to end.